2019
DOI: 10.1021/acsami.9b12398
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Endocytosis of Inorganic Nanoparticles with Zwitterionic Surface Functionalization

Abstract: PEGylation, which has traditionally been the method of choice to enhance the colloidal stability of nanostructures designed for biological applications, and to prevent non-specific protein adsorption, is now being challenged by short zwitterionic ligands. Inspired by the zwitterionic nature of cell membranes, these ligands have the potential to push forward the field of nanoparticles for nanomedicine. In this work, we report a thorough analysis of the surface chemistry of silica coated luminescent CdSe/CdS qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 41 publications
(94 reference statements)
0
22
0
1
Order By: Relevance
“…cancer cells) (Breus et al, 2009;Muro et al, 2010;Zhang et al, 2011). An example of the zwitterionic ligands useful to enhance NPs uptake is reported by Drijvers et al (2019). In this work, silica coated CdSe/CdS quantum dots were biofunctionalized with PEG and with sulfobetaines in order to evaluate the impact of these modifications on the NPs cellular uptake.…”
Section: Chemiluminescence Fluorescence Colorimetrymentioning
confidence: 99%
“…cancer cells) (Breus et al, 2009;Muro et al, 2010;Zhang et al, 2011). An example of the zwitterionic ligands useful to enhance NPs uptake is reported by Drijvers et al (2019). In this work, silica coated CdSe/CdS quantum dots were biofunctionalized with PEG and with sulfobetaines in order to evaluate the impact of these modifications on the NPs cellular uptake.…”
Section: Chemiluminescence Fluorescence Colorimetrymentioning
confidence: 99%
“…[118][119][120][121][122] Simply put, a successful surface functionalization boils down to finding the right balance between minimizing interactions with biological components that elicit an immune response (and hence premature clearance of the NPs), while prompting selective recognition and interaction with cells that form the tissue of interest. Silica coating, [123][124][125] as well as the use of zwitterionic molecules 126,127 or polymers 128 are amongst the most explored strategies to enhance biocompatibility and extend NP circulation time. Decoration with polyethylene glycol (PEG), in particular, is often regarded as the golden standard for imparting "stealth" properties to NPs.…”
Section: Surface Chemistrymentioning
confidence: 99%
“…Indeed, the use of zwitterionic coatings, due to their non-fouling and stealth properties, prevented cellular uptake and hence increased the circulation time of those NPs in vivo. However, Drijvers et al [72] found that the internalization could be tuned through the ligand density. For 15 nm QDs coated with a silica shell functionalized with sulfobetaines, substantial cellular uptake was detected by both confocal microscopy and flow cytometry when using up to 1 ligand per nm 2 .…”
Section: Zwitterionsmentioning
confidence: 99%
“…Fluorescence confocal microscopy images of zwitterion-functionalized quantum dots (QDs) (A) versus PEGylated QDs (B) and the correlation between a positive cell percentage (PCP) and ligand type and density (C). Reprinted with permission from reference[72]. Copyright (2019) American Chemical Society.…”
mentioning
confidence: 99%